Liberal leviathan : the origins, crisis, and transformation of the American world order - Ikenberry, G. John (Princeton studies in international history and politics., 2011)
In the second half of the twentieth century, the United States engaged in the most ambitious and far-reaching liberal order building the world had yet seen. This liberal international order has been one of the most successful in history in providing security and prosperity to more people. But in the last decade, the American-led order has been troubled. Some argue that the Bush administration, with its war on terror, invasion of Iraq, and unilateral orientation, undermined this liberal order. Others argue that we are witnessing the end of the American era. Liberal Leviathan engages these debates.